Protest and Resistance: Conceptualizing a Blackamerican Institutional Schema and the Contemporary Relevance of Pre- Educators - James Wright; Jennifer Karnopp (SAGE Publishing, 2024)
In the century following emancipation, Blackamericans developed robust and effective schools despite limited resources. Unfortunately, their successes and contributions to the education system are often overlooked. This interdisciplinary theoretical paper draws on historiographies of segregated school systems, examining the struggles of Blackamerican educators within segregated education systems through the lenses of coloniality and institutional work. This examination reveals a distinct Blackamerican institutional schema rooted in community, guiding educators in navigating structural and systemic dynamics that shape educational opportunities and successfully challenge dominant white education standards. We discuss the coloniality of schooling, a structural framework, and a mindset that continues to undergird our contemporary education system and then draw attention to an alternative perspective. Our goal is to work toward more inclusive and equitable education systems by recognizing and acknowledging the protest and resistance of Blackamerican educators, their contributions to alternative epistemologies, and the mindsets that guided their actions.